Comparative Analyses of the Dominant and Non-Dominant Upper Limbs during the Abduction and Adduction Motions - Haemi JEE; Jaehyun PARK (Tehran University of Medical Sciences, 2019)
Background: Asymmetry in repeated motion may lead to dyskinesia through imbalance in the involved musculoskeletal structures. The dominance sides are also involved greater movement involvement over the non-dominant sides. The upper limbs with multiple joints and largest range of motion are prone for unsynchronized coordination. Natural movement analysis is required for application to everyday activities. Methods: Thirty participants were first recruited from Inha University, Incheon, Korea in 2019. Twenty subjects were assessed for comparisons of asymmetrical motion between the dominant and non-dominant arms during the abduction and adduction lateral raises after excluding ten subjects for shoulder pain and left-handedness. Results: The abduction and adduction motions of the bilateral arms were compared for the angular locations, velocity, and acceleration for every 10 degrees. The angular locations of the dominant side occurred significant earlier in the initial (10°, 20°, 30°) phase and later in the last (10°, 20°) phase of abduction and adduction in comparison to the non-dominant side (P<.05). The angular accelerations of the dominant side were also significantly greater during the initial phase (0°, 10°, 30°) and last phase (0°, 10°, 30°) (P <.05). The angular velocities were significantly greater during the later phase (40, 50, 60°) of abduction (P <.04). Conclusion: Comparative dominant side indicated more controlled movements through the range of motion with greater stability in angular acceleration and deceleration especially during the initial and last phase of abduction and adduction, respectively. Training for control of the specific angular points should be considered during abduction and adduction motions to prevent asymmetry of the bilateral arms.